Transparent and conductive ZnO : Al thin films prepared by sol-gel dip-coating - Valle, G. G.; Hammer, Peter [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier B.V., 2004)
Aluminum doped zinc oxide polycrystalline thin films (AZO) were prepared by sol-gel dip-coating process. The sol was prepared from an ethanolic solution of zinc acetate using lithium hydroxide or succinic acid as hydrolytic catalyst. The quantity of aluminum in the sol was varied from 1 to 10 mol%. The structural characteristics studied by X-ray diffractometry were complemented by resistivity measurements and UV-Vis-NIR spectroscopy. The films are transparent from the near ultraviolet to the near infrared, presenting an absorption cut-off at almost 290 nm, irrespective of the nature of the catalyst and doping level. The best conductors were obtained for the AZO films containing 3 mol% of aluminum, prepared under acidic and basic catalysis and sintered at 450 degreesC. Their optical band-gap of 4.4 eV calculated from the absorption cut-off is larger than the values for band-gap widening predicted by the standard model for polar semiconductors. These polycrystalline films are textured with preferential orientation of grains along the wurtzite c-axis or the (100) direction. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: aluminum doping; conductivity; sol-gel; zinc oxide films